1997
DOI: 10.1046/j.1471-4159.1997.68041400.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Early Loss of Membrane Protein Kinase C Is a Necessary Step in the Excitatory Amino Acid‐Induced Death of Primary Cortical Neurons

Abstract: A rapid loss of protein kinase C (PKC) activity is a prognostic feature of the lethal damage inflicted on neurons by cerebral ischemia in vivo and by hypoxic and excitotoxic insults in vitro. However, it is not known if this inactivation of PKC is incidental or is an essential part of the neurodegenerative process driven by such insults. To address this issue, the effects of glutamate on PKC activity and neurotoxicity were studied in immature [8 days in vitro (DIV)] and mature (15-20 DIV) embryonic day 18 rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 36 publications
5
52
1
Order By: Relevance
“…PKC is a central protein in neuronal metabolism, function, and survival (Dekker and Parker, 1994), and changes in PKC activity have been hypothesized to play either a protective or a detrimental role in the cell death, including ischemic damage (Hara et al, 1990;Busto et al, 1994;Durkin et al, 1997). However, we could not detect any significant effects of various PKC inhibitors treated alone on hypoxia-reperfusioninduced necrosis in additional experiments (Fig.…”
Section: Pkc-␥ Activation In Insulin Signaling Prevents Necrosis 1031mentioning
confidence: 74%
“…PKC is a central protein in neuronal metabolism, function, and survival (Dekker and Parker, 1994), and changes in PKC activity have been hypothesized to play either a protective or a detrimental role in the cell death, including ischemic damage (Hara et al, 1990;Busto et al, 1994;Durkin et al, 1997). However, we could not detect any significant effects of various PKC inhibitors treated alone on hypoxia-reperfusioninduced necrosis in additional experiments (Fig.…”
Section: Pkc-␥ Activation In Insulin Signaling Prevents Necrosis 1031mentioning
confidence: 74%
“…Its loss of function, especially upon OS exposure, correlates with the severity of the damage (26,37). Therefore, we investigated the possible involvement of PKC in the neuroprotective activity of EGCG against 6-OHDA-induced neurotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…It is more likely that excitotoxic stimulation would trigger second messenger cascades, leading to post-translational modifications of existing membrane proteins or activation of a dormant channel to activate I EIC . Indeed, NMDA-dependent changes in protein phosphorylation Durkin et al, 1997), protease activity such as the calpains (Minger et al, 1998;Simpkins et al, 2003), and numerous other second messenger effects have been reported during glutamate excitotoxicity. Such alterations in key proteins or enzyme activities could result in the activation of the I EIC -Ca 2ϩ -permeable channel.…”
Section: Discussionmentioning
confidence: 99%